Prevalence and correlates of intimate partner violence among ever-married men in Uganda: a cross-sectional survey - Derrick Gubi; Stephen Ojiambo Wandera (BMC, 2022)
Abstract Background There is limited research on intimate partner violence (IPV) among ever-married men in Uganda. This paper aimed to establish the extent and correlates of emotional, sexual, and physical IPV among ever-married men in Uganda. Methods We used the 2016 Uganda Demographic and Health Survey (UDHS) data and selected a weighted sample of 2559 ever-married men. Frequency distributions were used to describe the characteristics of men and their partners. Chi-square tests and binary logistic regressions were used to identify factors associated with IPV among married men in Uganda. Results Almost half (44%) of the ever-married men experienced some form of IPV. Among the individual forms of IPV, emotional IPV was the most prevalent (36%), followed by physical IPV (20%) and sexual IPV the least common (8%). Factors that were associated with all the different forms of IPV included, region, number of wives, partners' controlling behaviors, witnessing parental violence, and drinking alcohol as well as the frequency of getting drunk by the female partners. Except for number of wives, which had a protective effect, the rest of the factors increased the likelihood of experiencing intimate partner violence among ever-married men in Uganda. Conclusions Besides women, men are also victims of intimate partner violence. This calls for combined efforts to reduce violence against men perpetrated by females by addressing controlling behaviors, frequency of getting drunk with alcohol, and lack of awareness of the issue. There is a need for interventions aimed at increasing public awareness to improve the reporting and case management of violence against men and boys.